Challenges in Diagnosis and Treatment of Pediatric Multiple Sclerosis - Lopes Silva, Rita (2016)
Keywords: Child; Demyelinating Autoimmune Diseases, CNS; Encephalomyelitis, Acute Disseminated; Multiple Sclerosis/diagnosis; Multiple Sclerosis/therapy.